A Mixed Methods–Grounded Theory Design for Producing More Refined Theoretical Models. (January 2021) - Shim, Minjung; Johnson, Burke; Bradt, Joke; Gasson, Susan
Current literature lacks explication of how traditional grounded theory and mixed methods–grounded theory (MM-GT) are similar/different and specific explication of how to construct MM-GT designs—our purpose is to do this. We illustrate the design process using a published study. Exploratory Phase 1 involves creation of a formative–theoretical model based on multiple implicit or explicit models identified in the literature, which are then combined into a single model using meta-modeling integration. Also, in Phase 1, a traditional grounded theory is developed "independently" using interview data. These two models are integrated into a combined/meta-model at the end of Phase 1. Confirmatory Phase 2 involves testing of the final Phase 1 meta-model using a mixed methods experiment. In Phase 3, the Phase 1 and Phase 2 results are integrated, producing the "final" meta-model. This article contributes to the field of mixed methods research by showing how to design an MM-GT study that is focused on theory development and testing.